2016
DOI: 10.4236/ajps.2016.79129
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Endogenous Hormonal Levels in Plants under Drought and Salinity

Abstract: The phytohormones are pivotal chemical messengers produced within the plant that regulate its growth and development, and responses to environmental stimuli. Drought and salinity are adverse environmental factors that disturb the plant hormonal balance. Accordingly, these hormonal fluctuations modify the cellular dynamic and hence they play a central role in regulating plant growth responses to abiotic stresses such as drought and salinity. The present review gives an update about the alterations of endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 92 publications
3
43
0
1
Order By: Relevance
“…Interestingly, the exogenous methylJA was found to repress the expression of the BR signaling and target genes (Gan et al, 2015). As expected (Huang et al, 2008; Llanes et al, 2016), drought stress induced the significant increase in the endogenous JA content in all analyzed genotypes. Interestingly, both the BR-deficient and BR-insensitive barley mutants retain the capacity of the significant increase in the endogenous JA content in reaction to drought, and relatively to even a higher extent when compared with the “Bowman” cultivar.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Interestingly, the exogenous methylJA was found to repress the expression of the BR signaling and target genes (Gan et al, 2015). As expected (Huang et al, 2008; Llanes et al, 2016), drought stress induced the significant increase in the endogenous JA content in all analyzed genotypes. Interestingly, both the BR-deficient and BR-insensitive barley mutants retain the capacity of the significant increase in the endogenous JA content in reaction to drought, and relatively to even a higher extent when compared with the “Bowman” cultivar.…”
Section: Discussionsupporting
confidence: 88%
“…In previous studies, mostly exogenous BRs applications were performed, thus the role of the endogenous BRs in the regulation of plant drought response remains controversial and requires further analysis (Jager et al, 2008; Llanes et al, 2016). In the present study the accumulation of two representatives of BRs, CS and 24-epiBL, was found to be significantly stimulated by drought in all analyzed genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations